Polymorphism of the Vitamin D Receptor Gene, Bone Mineral Density, and Bone Turnover in Postmenopausal Women from Lower Silesia (Poland) - Marek Demissie; Marek Bolanowski; Bozena Bidzinska; Urszula Tworowska; Katarzyna Zatonska (Elsevier, 2005)
Objective: Genetic factors are involved in determining bone mineral density (BMD) and in the pathogenesis of osteoporosis. There are relationships between various genetic polymorphisms and BMD or bone turnover. The aim of our study was to assess polymorphisms in the vitamin D receptor (VDR) gene (BsmI) in relation to BMD and bone turnover in a group of Polish postmenopausal women from the Lower Silesia region. Materials and Methods: BMD at the lumbar spine and proximal femur, bone turnover (osteocalcin and carboxyterminal cross-linked telopeptide of type I collagen, ICTP), and restriction fragment length polymorphism (RFLP) of the VDR gene using the BsmI restriction enzyme were examined in 116 postmenopausal women. Results: Despite the fact that we failed to detect statistically significant differences between the VDR genotypes in BMD, a trend towards higher BMD in women carrying allele b compared with wild-type subjects in our study is similar to previous reports. We also observed a higher allele b frequency in the control group (normal bone mass) compared with osteopenic/osteoporotic women (59.1% vs 40.0%). The lower activity of the resorption marker ICTP seen in allele b carriers could be involved. Conclusion: We report an association between VDR gene polymorphism and decreased BMD in Polish postmenopausal women from the Lower Silesia region, but this requires further robust studies for confirmation.